Study on the stall vortex and vibration characteristics in multi-stage pump under natural flow condition - Zhou, Runze (2023)
When a vessel reaches a specific speed, the circulating pump in the cooling system stops driving. It relies only on the kinetic energy its speed generates to provide cooling seawater for the condenser. This cooling strategy is known as natural flow cooling. Under natural flow conditions, the impeller rotates passively due to flow impact, and the circulating pump serves as a significant resistance component in the cooling system. The unstable flow within a pump is primarily attributed to the varying scales of stall vortex, which can induce vibration and potentially result in severe damage to components. To investigate the generation of stall vortex and vibration characteristics under natural flow conditions, the numerical simulation method was employed to study the structure and motion characteristics of stall vortex in multi-stage pumps at different flow rates. Moreover, vibration signals were collected through a natural flow experiment, and the obtained data were analyzed using empirical mode decomposition with singular value decomposition and wavelet transform methods. The result indicates that natural flow conditions can be categorized into impeller stuck and passive rotation. During passive rotation, the speed increases linearly with the flow rate. Thus, the blade inlet's attack angle remains consistent at different flow rates, making the internal flow features similar. The stretching and bending of the stall vortex structure primarily cause the variation of the vorticity. Additionally, the internal structure and motion pattern of stall vortex exhibit similarities. The excitation force increases continuously with the flow rate and is related to the effects of flow losses and turbulent kinetic energy. Vibration energy caused by stall vortex and rotor-stator interference is mainly concentrated in the low-frequency band.